Differences in accumulation of polycyclic aromatic compounds (PACs) among eleven broadleaved and conifer tree species. (December 2022) - Pleijel, H.; Klingberg, J.; Strandberg, B.; Sjöman, H.; Tarvainen, L.; Wallin, G.
Graphical abstract: Highlights: Leaf accumulation of PAHs and DBTs varied strongly among species. Conifers accumulated larger amounts of gaseous PAHs than broadleaved trees. Specific leaf area was important for gaseous PAH accumulation in leaves/needles. Accumulation of DBTs was similar to that of gaseous PAHs. Gaseous PAHs and DBTs were lost from deciduous trees between June and September. Abstract: PACs (polycylic aromatic compounds) are air pollutants formed in incomplete combustion, e.g., in vehicle engines. Vegetation can potentially remove substantial amounts and act as bioindicators of these pollutants. Increased knowledge of the pollutant removal efficiencies of different tree species is essential for understanding the potential benefits trees can provide urban residents. We investigated the leaf/needle content of the two PAC groups, polycyclic aromatic hydrocarbons (PAHs, 32 compounds) and dibenzothiophenes (DBTs, 6 compounds) in seven broadleaved and four conifer tree species in an arboretum of South-West Sweden. PAHs were grouped into low-molecular (L-PAHs, largely gaseous), medium-molecular (M-PAHs, both gaseous and particle-bound) and high-molecular mass (H-PAHs, largely particle-bound) PAHs. DBTs are organosulphur compounds with two benzene rings. In general, conifer needles were stronger accumulators of PACs than leaves of broadleaved trees. Comparing three-year-old and one-year-old needles showed that evergreen conifers accumulated L-PAHs, M-PAHs, H-PAHs and DBTs over several years. In deciduous trees, L-PAHs and DBTs declined from June to September, M-PAHs had no significant net change, but for H-PAHs, there was a significant net accumulation. Conifers had a similar or lower net average annual accumulation of H-PAHs than broadleaved trees, except the deciduous conifer Larix, which had the highest uptake rate of this toxicologically important PAH category. Our results suggest that L-PAH accumulation depends on leaf/needle mass or volume, while for H-PAHs leaf/needle area is more important. This explains why conifers represented a stronger sink for L-PAHs and M-PAHs. DBT accumulation in leaves/needles was similar to that of L-PAHs. An important conclusion is that tree leaves/needles accumulate substantial amounts of PAC with strong and complex contrasts between tree species and PAC groups. Another implication of our data is that conifer needles are useful as bioindicators for PAC pollution since they accumulate all PAC categories over several years.